Frequency and prophylaxis for taxanes-associated hypersensitivity reactions - Łojko, Anna; Markowska, Janina; Lubin, Jolanta; Litwiniuk, Maria; Mądry, Radosław (Contemporary Oncology/Współczesna Onkologia, 2002)
Taxanes, like other cytostatics, cause many common side effects. Moreover, these drugs are also associated with hypersensitivity reactions. The most frequent of these include skin reactions like rash or erythema, hypertonic or hypotonic blood pressure, fever, chills, chest pain and bronchospasm. There are also very rare fatal outcomes. This study evaluates the frequency of taxanes-associated hypersensitivity reactions in patients treated for breast and ovary cancer in the Department of Oncology in Poznań. From 1998 to 2002, 206 female patients were treated with taxanes. 695 courses of paclitaxel and 389 courses of docetaxel were given. Premedication was applied in all cases. Nine patients developed hypersensitivity reactions (4.4%). In three of them the treatment with taxanes was stopped, six patients continued treatment after appropriate precautions. The appearance of hypersensitivity is not a contraindication for treating with taxanes. In such cases we should co-administer diphenhydramine (or intramuscularly antazoline) and hydrocortisone intravenously and start taxanes infusion after complete disappearance of symptoms of previous reaction. In patients who developed a second episode of taxanes-associated hypersensitivity reaction, desensitization could be applied. These methods are very effective. Patients are able to receive successfully further therapy with taxanes.